Development and characterisation of polylactic acid/cinnamon bark oil films: Phenolic migration into various food simulants - Foong, Han Lyn; Sulaiman, Rabiha; Mohamad Azman, Ezzat; Ashari, Rozzamri; Saricaoğlu, Furkan Türker; Langowski, H.C.; Zainal Abedin, Nur Hanani (Elsevier, 2025)
In this study, polylactic acid (PLA)/cinnamon bark oil (CBO) films were prepared via solvent casting method and characterised for their physical, optical, mechanical, and antioxidant properties. A 15 % loading of CBO significantly (p < 0.05) improved the water vapour barrier, tensile strength, and elongation at break, while its effects on film thickness and water solubility were insignificant (p ≥ 0.05). At a 30 % CBO concentration, the films exhibited over 99 % UV light blockage at wavelengths of 200, 280, and 400 nm. Antioxidant assays demonstrated strong radical scavenging activities, with maximum DPPH and ABTS scavenging values of 93.30 % and 99.40 %, respectively. To investigate the behaviour of the PLA/CBO film and their antioxidant activities in various food systems, controlled phenolic migration studies were conducted using aqueous (10 % ethanol), lipophilic (50 % ethanol), and acidic (3 % acetic acid solution) food simulants. The migration results followed an exponential time-dependent trend, with the highest migration in 50 % ethanol, indicating the films’ efficacy in preventing oxidative deterioration in fatty foods. These findings demonstrate the potential of PLA/CBO films as active and sustainable packaging materials, offering enhanced barrier, mechanical, and antioxidant properties compared to pure PLA films, making them promising candidates for reducing food waste and extending product shelf life.